Support for decision-making on sharing health data for research: are data counsellors relevant?. (20th October 2021) - De Freitas, C; Silva, S; Machado, H; Baptista, MJ; Leão Teles, E; Maia, T; Amorim, M
Abstract: Background: The implications of sharing one's health data are far-reaching. Potential applications of health data range from the delivery of treatments tailored to individuals' characteristics to improvements in public health, while also posing concerns about privacy, social justice and equity. Making informed decisions about health data sharing thus requires thorough consideration of the scientific, ethical and personal implications of donations. This study assessed participants' preferences regarding decision-making about health data sharing for research, including the need for support by data counsellors. Methods: This observational cross-sectional study includes 159 patients and 479 carers followed at two reference centres for rare diseases in a Portuguese academic hospital, between June 2019 and March 2020. Participants were asked about preferred modes of decision-making: deciding on their own, deciding with support from another person, or delegating the decision to someone else. Those who responded the last two options also reported who they would choose for support or delegation: family or friends; a data counsellor; a professional with no specific training on data counselling; other. Data were analysed using descriptive and inferential statistics. Results: The majority of respondents would prefer to decide with support (62%), 37% would prefer to decide on their own and 1% would opt to delegate the decision of sharing health data. Among those who expressed a preference for support, 60% would like to rely on a data counsellor. Carers, older and higher educated participants, and those with upper white-collar occupations and who were satisfied with their own health were significantly more likely to select data counsellors as their preferred source of support when engaging in decision-making about health data sharing for research (p < 0.05). Conclusions: This study supports recommendations for the creation of a new professional specialty of health data counsellors. Key messages: Most participants express the need for support in making decisions about health data sharing for research, with 60% preferring support from a data counsellor. As a new professional specialism, health data counselling can help to advance informed public participation in health research.